2008
DOI: 10.1016/j.dnarep.2007.07.015
|View full text |Cite
|
Sign up to set email alerts
|

DNA mismatch repair-induced double-strand breaks

Abstract: Escherichia coli dam mutants are sensitized to the cytotoxic action of base analogs, cisplatin and Nmethyl-N'-nitro-N-nitrosoguanidine (MNNG), while their mismatch repair (MMR)-deficient derivatives are tolerant to these agents. We showed previously, using pulse field gel electrophoresis, that MMR-mediated double-strand breaks (DSBs) are produced by cisplatin in dam recB (Ts) cells at the non-permissive temperature. We demonstrate here that the majority of these DSBs require DNA replication for their formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(38 citation statements)
references
References 46 publications
(65 reference statements)
2
35
0
1
Order By: Relevance
“…Another recent study has demonstrated that MNNG induces replicationindependent DSBs in a dose and MMR-dependent manner, and does not require DNA replication. These replication-independent DSBs are proposed to be the result of overlapping BER and MMR tracts on complementary DNA strands [60]. Our experimental approach may also indicate increased DSB damage that is located at sites on the chromatin not associated with lesions recognized by MMR.…”
Section: Discussionmentioning
confidence: 77%
“…Another recent study has demonstrated that MNNG induces replicationindependent DSBs in a dose and MMR-dependent manner, and does not require DNA replication. These replication-independent DSBs are proposed to be the result of overlapping BER and MMR tracts on complementary DNA strands [60]. Our experimental approach may also indicate increased DSB damage that is located at sites on the chromatin not associated with lesions recognized by MMR.…”
Section: Discussionmentioning
confidence: 77%
“…In E. coli, homologous recombination is required for resistance to methylating agents that give rise to MMR-dependent DSBs. In dam recB(Ts) ada ogt cells exposed to MNNG, a subset of these DSBs are replication-dependent, and likely to be the primary contributor to cytotoxicity (Nowosielska and Marinus, 2008). Rapidly dividing cells were more sensitive to killing by MNNG than slowly growing cells consistent with a futile cycling model.…”
Section: Mmr and Dna Damage Signallingmentioning
confidence: 87%
“…If excision continued until a SSB on the opposite strand is reached, a DSB would be formed. A similar model has been proposed for Escherichia coli dam cells exposed to the methylating agent MNNG, in which DSBs arise when MMR excision on one strand encounters a nick generated by APE on the other (47). Depending on the orientation of the SSBs relative to each other, some DSBs created by MMR activity will be blunt and some will have 5Ј or 3Ј overhangs.…”
Section: Discussionmentioning
confidence: 99%